(untitled) (Iraqi Journal of Medical Sciences, 2004)
Background: Apoptotic cell death plays an important role in cell biology and pathology including studies of embryonic development, pathogenesis of diseases, and the response of cell to therapy. Aim of the study: To clarify the relation between apoptosis and oxidative stress in different pregnancy outcome, namely miscarriage and PET. Patient and methods: The study involved 30 pregnant women; 10 were preeclampsia, 10 had miscarriage (before 20 weeks gestation). Surface morphological changes of lymphocyte apoptosis were diagnosed by phase contrast and Interference contrast microscopy. Lipid peroxidation using thiobarbituric acid reactive species (malondialdehyde). Erythrocyte glutathione was estimated by Lang et al method, Zinc and Copper were estimated using atomic absorption spectrophotometer. Statistical analysis done using unpaired student T- test, and correlation coefficient. Results: We found a significant increase in lymphocyte apoptosis in preeclamptic patients (p<0.05) than normal pregnant, the increase in MDA level was highly significant p<0.005 the same thing applied to consumption of glutathione in preeclamptic patients p<0.005 .there was also positive correlation between increased apoptotic process and oxidative stress variables. In miscarriage there was a significant increase in lymphocyte apoptosis compared to normal pregnant (p<0.05) also there was strong positive correlation between apoptotic process and oxidative stress (r=0.92). Conclusion: Lymphocyte apoptosis and oxidative stress was significantly increased in PET and miscarriage; this means that oxidative stress can induce PET and miscarriage in pregnant women. Key words: apoptosis, oxidative stress, PET, miscarriage Iraqi J Med Sci, 2004; Vol. 3 (1):3-7